Aesthetcs is Truth on Being (Art According to Martn Heidegger) - Sunarto Sunarto (Program Studi Pendidikan Seni Pertunjukan FKIP ULM, 2017)
In his philosophy, the leter Heidegger attemped to gain a non-reifyingaccess of to Being. To this end he turned to art, especting it to makeprecisely Such access possible. His principal writing on aesthetics in theessay “The Origin of the Work of Art” (1935-1936). Kant, when writingon aesthetics, had investigated aesthetic experience, that is to say theeffect of works of art on the subject. In opposition to this, Heideggeremphasized in his essay the autonomous value of a work of art.According to Heidegger a work of aer most most not be misunderstoodas a thing with distinctive characteristics of its own such as, for instance,the fact that it depicts reality particulary well or particulary beautifully.On the contrary it reveals the general nature of thing, thereby openingup a view of the world for us.Keyword: art, aesthetics, being and time, heidegger